2022
DOI: 10.3390/insects13060552
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Use of Basil as a Functional Plant for the Biological Control of Aphids by Chrysopa pallens (Neuroptera: Chrysopidae) in Greenhouses

Abstract: Effective biological control agents that can provide sustainable pest control need to be researched in further detail; functional plants (or non-crop insectary plants), in particular, are garnering increased research interest. Much remains to be learned as to how non-crop plants can augment biological control in greenhouse systems. In this study, we combined laboratory and greenhouse assays to assess the extent to which basil (Ocimum basilicum L.) (Lamiales: Lamiaceae) affected the biological control of aphids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Studies had showed that combining attractive synthetically produced HIPVs with functional plants which provide alternative resources to the targeted natural enemies can attract and retain efficient natural enemies in crop fields ( Simpson et al., 2011 ; Jaworski et al., 2019 ). Lots of flowers play an important role in increasing fitness in predatory natural enemies ( Wang et al., 2020 ; Fang et al., 2022 ). Flowers of Perilla frutescens , mixed with prey, have a positive effect on H. axyridis survival and early reproduction ( Hatt and Osawa, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies had showed that combining attractive synthetically produced HIPVs with functional plants which provide alternative resources to the targeted natural enemies can attract and retain efficient natural enemies in crop fields ( Simpson et al., 2011 ; Jaworski et al., 2019 ). Lots of flowers play an important role in increasing fitness in predatory natural enemies ( Wang et al., 2020 ; Fang et al., 2022 ). Flowers of Perilla frutescens , mixed with prey, have a positive effect on H. axyridis survival and early reproduction ( Hatt and Osawa, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such findings are confirmed by Osman et al (2017) and Abou El-Saad (2018). Previous studies have reported an association between the presence of sweet basil plants and the colonization rates and population persistence of lacewing by assessing how sweet basil, as a functional plant, affects the lacewing under laboratory and greenhouse conditions and found that the presence of sweet basil enhanced the fitness attributes of lacewing as compared with control treatments (Fang et al 2022). Furthermore, the attractiveness of sweet basil plants and another four floral plants to three predator species and found that P. alfierii showed its maximum preferability rate to sweet basil flowers (Abd El-Kareim et al 2011).…”
Section: Seasonal Abundance Of the Main Piercing-sucking Insect Pests...mentioning
confidence: 99%
“…The lacewing, Chrysopa pallens (Neuroptera: Chrysopidae), is a common predatory insect in agroforestry ecosystems in Asian and European regions. Both adults and larvae forms of can feed on aphids, thrips, and eggs and larvae of lepidopterans, effectively controlling the occurrence of pests (Ali et al, 2018; Fang et al, 2022; Winterton & Freitas, 2006; Yu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%